MORTALITY AND MORBIDITY IN PERFORATIVE PERITONITIS AND ITS SIGNIFICANCE (International Journal of Food and Nutritional Sciences, 2022)
“Early prognostic assessment of abdominal sepsis is necessary in order to identify high-risk patients for more aggressive therapeutic treatments, offer objective categorization of illness severity, and determine the best perioperative management techniques. Perforations of the proximal gastrointestinal tract were six times more common than perforations of the distal GI tract, according to previous studies from India, which contrasts sharply with studies from developed countries such as the United States,(5) Greece, and Japan, which revealed that distal gastrointestinal tract perforations were more common. (6) The time of presentation to the hospital, early surgical intervention, and perioperative care all have a role in the outcome of perforated peritonitis.”“The goal of the operating protocol is to repair the pathology while avoiding any significant mishaps and to use a surgical method with few consequences. Following initial resuscitation with high volumes of crystalloids and administration of wide spectrum antibiotics against gramme negative bacteria and anaerobes, laparotomy and peforation closure are frequently performed”.